Fazlur Rahman's Hermeneutic Analysis of Hamka's Tafsir al-Azhar - Saputri, Rahmah Eka (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
TafsÄ«r al-Azhar by HAMKA is a work of Malay tafsÄ«r that exists to answer social problems in the Indonesian context in the era when HAMKA lived. Therefore, contextualization is the dominant feature in HAMKA's interpretation; it is considered in line with Fazlur Rahman's double movement hermeneutic principle. This research is a literature review analyzing TafsÄ«r al-Azhar by HAMKA using Fazlur Rahman's double movement hermeneutic perspective to find compatibility between the two. In general, this research finds that, in TafsÄ«r al-Azhar, HAMKA applies Fazlur Rahman's double movement hermeneutic method; especially when he attempts to get in and answer current issues by taking the main Qur'an principles through the intertextuality process and exploring the sociohistorical setting of a verse.